(untitled) (Research, Society and Development, 2020)
According to legislation for identity and quality, fruit pulp is the unfermented, non-concentrated product, the consumption of polished fruits, by an appropriate technological process with a minimum content in suspension. Objective to evaluate the quality of frozen pineapple pulps sold in Limoeiro do Norte - Ce. To do so, Physico-chemical and microbiological analyzes were carried out on four commercial pineapple flavor brands named (A, B, C and D). The characteristics analyzed were color, pH, soluble solids, titratable acidity, total sugars and vitamin C. The microbiological tests consisted of determining the probable number of molds and yeasts, total and thermotolerant coliforms and Salmonella. The data were subjected to analysis of variance and media compared by the Tukey test at 5% significance level. The results obtained indicate that the physicochemical point of view of the values found for pH, SS, acidity and sugars is the total of all analyzed brands, which are evaluated in accordance with the values recommended by the legislation, except in relation to the vitamin C content, as the values found for brand B and C are above the established limits. In the evaluation of the microbiological profile, all samples are applied within the microbiological standards RDC No. 12, of January 2, 2001, for values of coliforms and salmonella, demonstrating that they are using consumption statistics only regarding mold and yeast counts, while only the D brand was found to be within the defined standards.